Action Environment Potential by the Private Higher Education within Tertiary LL Dikti III for the SN Dikti Implementation - Sofyan, Muhammad (JPAS (Journal of Public Administration Studies), 2021)
Today, private universities are required to have competitiveness, independence, sustainable reach, integrated information network, in order to maintain the quality of higher education. In fact, not all tertiary institutions have plenty of qualified resources to meet these demands. The emergence of changes in meso policy on higher education standards (SN Dikti) became a substantial influence for private tertiary institutions. Private tertiary institutions are urged to be able to adjust even beyond the standards of tertiary institutions that have been prepared by the central government. The external environment and any amendments to regulations for higher education meso policies may affect the choice of actions and institutional decisions in the operational process of higher education in terms of adapting with and adopting institutions. Exploration of sundry field findings of this study has revealed several aspects to view, it’s how the regulations become a highly influential elements, organizational culture and work culture of other institutions, national, regional and global insights, the influence of inter-institutional cooperation, and assessment of international accreditation.